Interoceptive Awareness and Anorexia Nervosa: When Emotions Influence the Perception of Physiological Sensations. Issue 5 (May 2022) - Wollast, Robin; Fossion, Pierre; Kotsou, Ilios; Rebrassé, Audrey; Leys, Christophe
Abstract: Anorexia nervosa (AN) is related to difficulties in emotion regulation, including a deficit in interoceptive awareness. The lack of interoceptive awareness is considered a vulnerability involved in the development and maintenance of anorexic symptoms. Surprisingly, no study has been conducted that focuses on these associations in an emotional context. This study measures the interoceptive awareness—using heartbeat self-counting and a sphygmomanometer—of 25 subjects suffering from AN and 25 control subjects, first at rest and then in an emotional situation. The results show that a deficit in interoceptive awareness was observed for the subjects suffering from AN at rest as well as when an emotional context was induced. This study encourages future investigations to focus on the impact of interoceptive deficit in AN to develop as efficient a care regimen as possible for these subjects.